Integration of Global Analyses of Host Molecular Responses with Clinical Data To Evaluate Pathogenesis and Advance Therapies for Emerging and Re-emerging Viral Infections - Falcinelli, Shane D. (ACS Infect Dis, 2016)
[Image: see text] Outbreaks associated with emerging and re-emerging viral pathogens continue to increase in frequency and are associated with an increasing burden to global health. In light of this, there is a need to integrate basic and clinical research for investigating the connections between molecular and clinical pathogenesis and for therapeutic development strategies. Here, we will discuss this approach with a focus on the emerging viral pathogens Middle East respiratory syndrome coronavirus (MERS-CoV), Ebola virus (EBOV), and monkeypox virus (MPXV) from the context of clinical presentation, immunological and molecular features of the diseases, and OMICS-based analyses of pathogenesis. Furthermore, we will highlight the role of global investigations of host kinases, the kinome, for investigating emerging and re-emerging viral pathogens from the context of characterizing cellular responses and identifying novel therapeutic targets. Lastly, we will address how increased integration of clinical and basic research will assist treatment and prevention efforts for emerging pathogens.